Obsessed [large type] - Patterson, James, 1947-; Born, James O. (Patterson, James, 1947- Detective Michael Bennett thriller, 2023)
Aboard a police boat on the Hudson River, Detective Michael Bennett casts a wary eye into the cold, rough water. NYPD is searching for a murder victim-a young college student. They find her tossed in the dark waves, dressed for a night out in a sparkly black gown. The gruesome sight fills Bennett with the dread only a father could fathom. As the obsessive killer extends his spree, a pattern emerges. One that Bennett's eldest daughter fits to a disturbing degree. Now NYPD's top detective must lure the murderer into the light of day before the next deadly strike lands closer to home than Bennett could ever bear-as a parent, or as a protector.